The Relationship Between The Level Of Knowledge And Attitude Of Nurses Regarding Pain Management And Compliance With Documentation Of Pain Assessment In Patients At The Inpatient Installation Of The Rejang Lebong District Hospital, Bengkulu Province In 2024 - Mustakim, Teguh Ananda; Suyanto , Jipri; Azissah, Danur (Utami Publisher, 2025)
According to the National Hospital Accreditation Standards (2017), pain documentation is a record of pain felt by patients, carried out by the medical team, especially nurses. Documentation of pain assessment is useful for understanding the patient's response to the provision of care, treatment, and services and to determine whether the care decisions given are adequate and effective. This study aims to determine the correlation between the level of staff nurses’ knowledge and attitude about pain management and compliance with pain assessment documentation in patients at the Inpatient Installation in RSUD Rejang Lebong Regency of Bengkulu Province in 2024. The method in this study used a cross-sectional design. The population in this study were all staff nurses in at the Inpatient Installation in RSUD Rejang Lebong Regency, totaling 84 people. The sample was taken using the Total sampling method with a sample of 84 respondents. Data collection was obtained from respondents according to the number of samples that had been determined. The results of the univariate analysis showed that most of the respondents 53 (63.1%) had good knowledge and attitudes about pain management, most of the respondents 59 (70.2%) had compliance with pain assessment documentation, and almost half of the respondents answered that nurse interaction with patients was lacking (46.3%). The results of the bivariate analysis explained that the analysis of the correlation between the level of staff nurses’ knowledge and attitude about pain management and compliance with pain assessment documentation in patients at the Inpatient Installation in RSUD Rejang Lebong Regency in 2024 was seen using the Chi- Square test (Pearson Chi-Square) obtained a p value = 0.001, because the p value ≤ 0.05 then the decision taken was Ha accepted and H0 rejected, therefore the conclusion: there is a significant correlation between the level of staff nurses’ knowledge and attitude about pain management and compliance with pain assessment documentation in patients at the Inpatient Installation in RSUD Rejang Lebong Regency in 2024.